Physical Activity and Health-Related Quality of Life (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
The study aimed to evaluate the relationship between physical activity, psychological well-being, and Health-Related Quality of Life (HRQoL) among adults within the academic community of Universitas Pendidikan Indonesia. This research was designed to inform policymakers on the importance of implementing needs-based health services and improving overall health status.A total of 201 employees were selected as the sample population. To collect data, the researchers used the Global Physical Activity Questionnaire (GPAQ) and the Short Form Health Survey (SF-36). The results indicated that the data followed a normal distribution, with Kolmogorov-Smirnov test results for GPAQ = 0.82 and HRQoL = 0.83.The correlation test revealed a significant relationship between physical activity levels and HRQoL, with a significance value of Sig. = 0.000, which is less than 0.05, indicating statistical significance. The R-Square value of 0.694 suggests that a substantial portion of the variance in HRQoL can be explained by the level of physical activity.The study underscores the critical role of developing effective physical activity programs to influence and predict physical activity behaviors positively. The findings align with existing research that demonstrates the benefits of physical activity in enhancing HRQoL, improving mood, and reducing symptoms of depression. This highlights the importance of physical activity as a key factor in promoting psychological well-being and overall quality of life.